Association of late leaf spot (LLS) and rust resistance with yield in selected peanut genotypes: Association of late leaf spot (LLS) and rust resistance with yield in selected peanut genotypes - N RAMYA SELVI,; P L VISWANATHAN,; S MANONMANI,; L RAJENDRAN,; S SUNDRAVADANA, (Journal of Oilseeds Research, 2020)
In this study, seventy five peanut genotypes of groundnut were analyzed for association between diseaseresistance and kernel yield in kharif under two locations (Coimbatore and Aliyar Nagar). The result indicated nonsignificant association between the disease severity and yield.